Conventional Families: some criteria for kindergarten (Journal of Parents and Teachers, 2014)
Supporting or nor discriminating the different types of families is the aim of this article. Family’s most important role is protection, therefore, we all have responsibilities within, to back up and create an appropriate context for living together and having healthy relationships between each other to fulfill everyone’s necessities.
Keywords: family and school; family and education; pre-school education; educational psychology.